2018
DOI: 10.1053/j.ajkd.2017.12.012
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Trial of a Multicomponent Intervention to Promote Medication Adherence: The Teen Adherence in Kidney Transplant Effectiveness of Intervention Trial (TAKE-IT)

Abstract: Registered at ClinicalTrials.gov with study number NCT01356277.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(155 citation statements)
references
References 52 publications
2
147
1
5
Order By: Relevance
“…Inclusion of adherence data in a national quality registry can help identify high‐risk patients and open up for evaluating prospective intervention studies to improve adherence in specific populations in a proper way. Further studies should focus on implementation of adherence‐promoting interventions .…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of adherence data in a national quality registry can help identify high‐risk patients and open up for evaluating prospective intervention studies to improve adherence in specific populations in a proper way. Further studies should focus on implementation of adherence‐promoting interventions .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies evaluating adherence-related interventions in AYAs with other chronic conditions have likewise used shorter baseline monitoring periods relative to the intervention. 25,26 Participants also completed weekly questionnaires addressing reasons for nonadherence.…”
Section: Designmentioning
confidence: 99%
“…High CV TAC may reflect a number of factors, including adherence to prescribed medical regimen, barriers to laboratory services (timing and ability to get to laboratory), and variations in medical provider clinical patterns pre‐ and post‐transfer. Prior studies utilizing electronic monitoring of TAC intake in kidney transplant recipients found no association between TAC trough level variability and adherence to their medical regimen . As previously discussed, there may be an influence of number of TAC levels, as well as the effect of a medical provider changing TAC trough targets pre‐ and post‐transfer of care which contributes to variability of TAC levels.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies utilizing electronic monitoring of TAC intake in kidney transplant recipients found no association between TAC trough level variability and adherence to their medical regimen. 21,22 As previously discussed, there may be an influence of number of TAC levels, as well as the effect of a medical provider changing TAC trough targets preand post-transfer of care which contributes to variability of TAC levels. Therefore, we cannot suggest a causal pathway, but rather point out a relationship between high CV TAC and allograft loss.…”
Section: Discussionmentioning
confidence: 99%